Perlindungan Hak Konstitusional Masyarakat Hukum Adat Minangkabau dalam Pelaksanaan Gadai Tanah Pertanian - Aermadepa, Aermadepa (Jurnal Konstitusi, 2016)
This research aims to knowing implementation of Constitutional Right of Indigenous People in Agricultural Land Pawning According to Custom in Minangkabau West Sumatra. In Indonesia Agricultural Land Pawning be regulated in the Law No. 56 Prp 1960, where in Article 7 section 2 limits liens that have been implemented within seven years to be returned to the owner without ransom. This poses a problem in the implementation in the Minangkabau, because according to Minangkabau customary law, liens are to be redeemed regardless of the time period. this research is an emperical law research or sosiological (socio legal research). The result of this research knowing that On one hand the Indonesian 1945 Constitution acknowledges the existence of the rights of indigenous people, but on the other hand there are laws and regulations that are counterproductive to the guarantee of the mentioned rights. The implementation of agricultural land pawning in West Sumatra Minangkabau is not a bonded labor system that requires extortion but rather a system based on mutual help and pawn prices nearly equalize the price of the land. The application of Article 7 (2) of Law No.56 Prp 1960 is certainly harmful to the constitutional rights of Indigenous Minangkabau people.